2020
DOI: 10.1021/acs.energyfuels.0c00122
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Catalytic Oxidation of NO in Coal Combustion Flue Gas over Co-Doped Mn–Ti Oxide Catalyst

Abstract: The coprecipitation method was used to prepare Mn/Ti, Mn/Co/Ti, and Co/Ti metal oxide catalysts to oxidize NO with O 2 . The influence of the concentrations of NO and O 2 on the oxidation of NO was investigated. Besides, the changes in the reaction rate with the particle size of the catalysts were investigated to determine the internal diffusion resistance. The surface area and microcrystalline structure of the catalysts were analyzed to investigate the impact of physical structure on SO 2 poisoning in the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The traditional catalysts might be prematurely aged and inactivated in the complex industrial gas atmosphere (including SO 2 , CO 2 , H 2 O, and so on). 19,20 Therefore, it is very important to design suitable catalysts that can deeply oxidize the pollutants and simultaneously keep stable efficiency under industrial conditions. 21 In this manuscript, we summarize the latest related progress on the stability enhancement for the catalytic removal of CO, CH 4 , and VOCs in terms of the long-term durability, resistance to sinter, and tolerance for multi-impurities (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional catalysts might be prematurely aged and inactivated in the complex industrial gas atmosphere (including SO 2 , CO 2 , H 2 O, and so on). 19,20 Therefore, it is very important to design suitable catalysts that can deeply oxidize the pollutants and simultaneously keep stable efficiency under industrial conditions. 21 In this manuscript, we summarize the latest related progress on the stability enhancement for the catalytic removal of CO, CH 4 , and VOCs in terms of the long-term durability, resistance to sinter, and tolerance for multi-impurities (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The original electronic structures of the catalysts may be changed by metal doping so as to produce better catalytic properties. In this perspective, the Fe-doping can improve the OER activity dramatically . Qiu et al reported that the Fe-CoOOH/G nanohybrids acted as a catalyst for OER.…”
Section: Introductionmentioning
confidence: 99%
“…In current studies, some scholars have tried to load some other catalyst components (Ce-and Mn-based metal oxides) on the surface of the solid adsorbent to take advantage of the excellent pore structure for catalytic reduction or catalytic oxidation reactions here to remove NO. 35,36 Wet de-NO x refers to the direct absorption of NO with liquid absorbents, mainly including water, dilute nitric acid, alkaline solutions, complexing absorbents, etc. The absorption principles and conditions of each absorbent are various from one to another, resulting in significant differences in the application range.…”
Section: Study Of De-no X Methodsmentioning
confidence: 99%
“…This method requires a very large amount of adsorbent but with a limited efficiency, and regeneration of the adsorbent is difficult, with it gradually being phased out in practical industrial applications. In current studies, some scholars have tried to load some other catalyst components (Ce- and Mn-based metal oxides) on the surface of the solid adsorbent to take advantage of the excellent pore structure for catalytic reduction or catalytic oxidation reactions here to remove NO. , …”
Section: Study Of De-no X Methodsmentioning
confidence: 99%